Isolation of Circulating Biomarkers for Liquid Biopsy using Immunoaffinity‐Based Stimuli‐Responsive Hybrid Hydrogel Beads. Issue 3 (22nd June 2021) - Kang, Yoon‐Tae; Kim, Young Jun; Rupp, Brittany; Purcell, Emma; Hadlock, Thomas; Ramnath, Nithya; Nagrath, Sunitha
Abstract: This work presents chemically stable and biodegradable hydrogel beads for the isolation of circulating tumor cells (CTCs) and circulating exosomes in liquid biopsy. The liquid biopsy hydrogel beads ( LB beads) consisting of alginate and poly(vinyl alcohol) hydrogels show both chemical stability and stimuli‐degradable characteristics. Unlike single‐component hydrogels, this hybrid form is not easily degraded by buffers or cell culture media while its degradable characteristic remains; thus, it is useful in bio‐applications requiring multi‐step processes with various reagents and lengthy incubation periods. We applied our platform to clinical samples for isolating two promising circulating biomarkers for a liquid biopsy, CTCs and exosomes, by conjugating the hydrogel surface with anti‐EpCAM and anti‐CD63 antibodies, respectively, thus achieving 37.4 CTCs and comparable amount of exosome recovery per 1 milliliter of blood. The results show easy device‐free isolation and retrieval of CTCs and exosomes, with recovered circulating biomarkers successfully analyzed by western blot analysis and fluorescence microscopy. We believe that this simple and versatile platform enables us to isolate prominent circulating biomarkers for clinical use in cancer diagnosis. Abstract : Circulating markers isolation using hydrogel‐beads : this work reports a hybrid hydrogel platform facilitating isolation of two promising liquid biopsy biomarkers, circulating tumor cells and circulating exosomes. The results show easy device‐free isolation and retrieval of CTCs and exosomes, with recovered circulating biomarkers successfully analyzed by western blot analysis and fluorescence microscopy. This simple and versatile platform makes it possible to isolate prominent circulating biomarkers for clinical use in cancer diagnosis.